LINGUISTIC VARIATION REFLECTED ON INDONESIAN TRUCK GRAFFITI (SEMIOTIC STUDY) - Winda Titi Putri Ningtias; Emy Sudarwati (Erudio Journal of Educational Innovation, 2021)
The objective of this study was to analyze the abnormality of language use by Indonesian truck drivers in using phoneme and unique way of interpreting. This study uses a qualitative analysis of text content. The data of this study are graffiti texts displayed on Indonesian truck. They were collected from some websites and social media. The relation of sound- meaning was analyzed by using Homophonic Translation, Functional Grammar, Saussurean and Barthesian Semiotic concept. The results of this study show Soramimi between English and Indonesian Native languages such as Javanese, Betawi, or Sundanese from 27 truck graffiti texts. There are three out of 27 data were grammatically accepted in both languages. There are 3 vowels and 4 consonants pronunciation tendency. There are reduction and addition in some words to fit the Indonesian language. The reason this data exist is that the truck community want to amuse people on the road by showing unique language use through moving exhibition.